Implementasi Pengadaan Obat Berdasarkan Permenkes RI Nomor 63 Tahun 2014 di Dinas Kesehatan Kabupaten Pelalawan Tahun 2018 - Ummi Kalsum (LPPM Universitas Muhammadiyah Riau, 2019)
In health, medicine saves lives and improves the quality of health. Access to medicines is a human right. Permenkes RI No. 63 of 2014 reads To ensure the availability of medicines work units in the health sector are responsible for medicine procurement. In the Dinkes Kabupaten Pelalawan in 2018, the realization of the DAK fund budget was 90.26%, the availability of drugs was 75.78% and 10 SPK had disbursement problems. Research Objectives To find out the problem and the implementation of drug procurement based on the Permenkes RI No. 63 of 2014 in the Dinkes Kabupaten Pelalawan in 2018. Qualitative and Descriptive Design. held from January to July 2019 with 5 informants. The result is lack of human resources, lack of policy socialization, lack of infrastructure. Implementation of Medicine Procurement is carried out based on the Permenkes RI No. 63 of 2014. Obstacles from providers such as lacking or slow response, drug items available in e-catalogs are inadequate, there is a time limit of absorption, the drug cannot be distributed due to stock vacancy, changes in composition, and drugs that are nearing expired.